Analisis Kinerja Lalu Lintas Simpang Tak Bersinyal untuk Penentuan Tingkat Pelayanan di Jalan Klampis Jaya Surabaya - Dwi Prastya Nurcahaya; R Endro Wibisono (Proceedings Series on Physical & Formal Sciences, 2021)
Klampis Jaya Road, Surabaya City, has a fairly heavy traffic flow, especially during working hours. This resulted in congestion on Klampis Jaya Road and not a few motorists who violated traffic regulations such as turning around Mleto Road. This study aimed to determine the current traffic flow performance and in 2024 at the intersection on Klampis Jaya Road, Surabaya City, predicted the traffic flow performance around the road and intersection on Klampis Jaya Road Surabaya City. The research method used was non-signalized intersection analysis using the Indonesian Road Capacity Manual. The calculation of the traffic performance of the four intersections in Klampis Jaya showed the Degree of Saturation (DS) and Service Level (TP) of each intersection. Traffic performance for the four intersections in 2021 was DS = 0.752 and TP = C (Enough), with the characteristics of stable traffic flow, was restricted movement. The traffic performance for the four intersections in 2024 was DS = 0.95 and TP = D (Less), with the characteristics of traffic flow stable movement being limited.